1982
DOI: 10.1002/star.19820340704
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solutes on the Gelatinization Temperature Range of Potato Starch

Abstract: The gelatinization behaviour of potato starch in an excess of water or solutions of sugars, other organic hydroxy compounds, or various inorganic salts was studied. The distribution of water and solutes between the external phase and the starch granules was measured by refractometry and a dye exclusion technique. When the limited water uptake of native starch granules is taken into account, the cooperative nature of gelatinization and the effect of water content on gelatinization behaviour can be explained sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
138
0
7

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 349 publications
(161 citation statements)
references
References 18 publications
16
138
0
7
Order By: Relevance
“…The changes that take place during gelatinization have been attributed to water availability (9), crystal stability within granules (25), differences between amorphous and crystalline regions (26), and glass transition related progressive melting (27). However, aspects of these explanations are contradictory, and it is believed that enthalpic transitions during gelatinization represent numerous changes in starch granules (6).…”
Section: Resultsmentioning
confidence: 99%
“…The changes that take place during gelatinization have been attributed to water availability (9), crystal stability within granules (25), differences between amorphous and crystalline regions (26), and glass transition related progressive melting (27). However, aspects of these explanations are contradictory, and it is believed that enthalpic transitions during gelatinization represent numerous changes in starch granules (6).…”
Section: Resultsmentioning
confidence: 99%
“…Starch gives a biphasic endotherm during gelatinization at low moisture levels (water:starch volume fractions less than 0.45) (Donovan, 1979;Evans and Haisman, 1982;Nakazava et al• 1984). Donovan (1979) suggested that in the presence of less water, theendothermic transition is characterized as a solvent-aided melting of crystallites in the starch granules.…”
Section: Amylose Leachingmentioning
confidence: 99%
“…When excess water is present, the high temperature transition disappears (Donovan, 1979). Evans and Haisman (1982) proposed the "cooperative melting theory", which explains the bi-phasic endotherm as a result of crystallite stability within the granules. The granules containing the least stable crystallites start to change first upon heating.…”
Section: Amylose Leachingmentioning
confidence: 99%
See 2 more Smart Citations